Isolated popliteus tendon injury in a male professional tennis player - Branche, G. C. (2000)
This is the story of a 24-year-old male touring professional tennis player having suffered a twisting injury to his flexed right knee about 10 days prior to his visit at the doctors. He had continuous pain in the postero-lateral aspect of the knee, associated with difficult terminal extension. There were no complaints of swelling, locking, or giving way. He had continued to play since the injury, but had noticed a progressive impairment. The result in this tournament was a second round loss. Treatment had consisted of protected bracing, intermittent modalities, stretching exercises, and anti-inflammatories under the guidance of the ATP Tour athletic training staff. The player had no history of prior knee problems and no other complaints. Physical examination showed a male who appeared to be in good health, with no gross atrophy or asymmetry of the lower extremities. No effusion was present. The range of motion was 0-135 degrees, which equalled the left knee. There was palpable fullness in the postero-lateral aspect of the knee, but this did not have the classic fluctuant consistency of a Baker's cyst. The terminal 10-15 degrees of extension elicited increased posterior pain. The patello-femoral joint had painless crepitation with no instability. Clinically the collateral and cruciate were stable. Resisted external rotation was painful postero-laterally, just below the joint line. Appley's compression test and McMurray's manoeuvre were negative. The patient had normal neuro-vascular status. At the time, my impression was a postero-lateral corner strain with the possibility of a torn lateral meniscus. X-rays and an MRI were performed when the symptoms persisted. Review of the X-rays showed a skeletally mature knee with no signs of alignment problems, degenerative changes or acute bony trauma. An incidental finding was that of a small to moderate-sized non-ossifying fibroma of the distolateral femoral metaphysis. The MRI was reviewed, and at first showed only some local haemorrhage in the lateral aspect of the lateral femoral condyle. Special coned-down views then revealed a tear of the popliteus tendon. Ligament structures and menisci were normal. A popliteus tendon injury to the right knee was diagnosed, with intact ligaments and menisci.